Embedded systems hardware, design, and implementation - Iniewski, Krzysztof (John Wiley & Sons, Inc., 2013)
"The book begins with an introduction of embedded computing systems, honing in on system on a chip (SoCs), multi-processor System-on-Chip (MPSoCs) and Network operation centers (NoCs). It covers on-chip integration of software and custom hardware accelerators, as well as fabric flexibility, custom architectures, and the multiple I/O standards that facilitate PCB integration. The second portion of the book focuses on the technologies associated with embedded computing systems. It also covers the basics of field-programmable gate array (FPGA), digital signal processing (DSP) and application-specific integrated circuit (ASIC) technology, architectural support for on-chip integration of custom accelerators with processors and O/S support for these systems. The third area focuses on architecture, testability and computer-aided design (CAD) support for embedded systems, soft processors, heterogeneous resources, on-chip storage. The final section covers software support, in particular O/S (linux, research and technology organization (RTO))"--